On the fragility of fractional-order PID controllers for IPDT processes - Padula, Fabrizio; Visioli, A. (2017)
© 2017 IEEE. This paper investigates the fragility (both from the stability and performance point of view) of (optimally tuned) fractional-order P(I)D controllers applied to integral processes. Indeed, the effects of the variations of the controller parameters are investigated in order to understand if the fine tuning of the controller is a critical issue. Both the set-point response and the load disturbance rejection tasks are considered. A comparison with standard integer-order P(I)D controllers is also performed.